Visual Illusions on the Internet: 15 Years of Change in Technology and User Behaviour. (September 2014) - Bach, Michael
Looking back over 15 years of demonstrating visual phenomena and optical illusions on the Internet, I will discuss two major topics. The first concerns the methodology used to present interactive visual experiments on the web, with respect to (a) wide accessibility, ie independent of browser and platform, (b) capable and elegant graphic user interface, (c) sufficient computational power, (d) ease of development and, finally, (e) future-proofing in an ever-changing online environment. The second major topic addresses some aspects of user behaviour, mainly temporal patterns (eg changes over weeks, years, long term), which reveal that there are more visitors during office hours.